2004
DOI: 10.1259/bjr/83720350
|View full text |Cite
|
Sign up to set email alerts
|

Radiprotective effect of abana, a polyherbal drug following total body irradiation

Abstract: Effects of 20 mg/kg body weight of abana (ABE) on radiation-induced sickness and mortality in mice exposed to 7 Gy to 12 Gy of gamma irradiation were studied. Treatment of mice with abana 1 h before irradiation delayed the onset of mortality and reduced the symptoms of radiation sickness when compared with the non-drug treated irradiated controls (double distilled water, DDW). Abana provided protection against both the gastrointestinal and haemopoietic deaths. However, animals of both the ABE+irradiation and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…It was reported that γ irradiation of mice results in a statistically significant two- to threefold increase in serum nitrate concentration 2.5–3.0 h postirradiation that returns to baseline after 12 h (32). This nitrate increase is consistent with the effect in mice of sublethal γ -radiation exposure on nitric oxide (NO) synthesis in the liver, intestine, lung, kidney, brain, spleen and heart (33), on increased hepatic nitrite concentration and peroxidative damage (34), and on attenuated hepatic glutathione concentration (34, 35). There is abundant evidence therefore that γ irradiation of mice increases hepatic NO synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…It was reported that γ irradiation of mice results in a statistically significant two- to threefold increase in serum nitrate concentration 2.5–3.0 h postirradiation that returns to baseline after 12 h (32). This nitrate increase is consistent with the effect in mice of sublethal γ -radiation exposure on nitric oxide (NO) synthesis in the liver, intestine, lung, kidney, brain, spleen and heart (33), on increased hepatic nitrite concentration and peroxidative damage (34), and on attenuated hepatic glutathione concentration (34, 35). There is abundant evidence therefore that γ irradiation of mice increases hepatic NO synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…To avoid potentially confounding side effects from the cytotoxicity of PFTα, we chose cPFTα as an equivalent alternative, as a reference for vanadate in our mouse study. We used 8 and 12 Gy of total body IR (TBI), which induce, respectively, hematopoietic and gastrointestinal syndrome in ICR mice (33)(34)(35)(36). For the i.p.…”
Section: Resultsmentioning
confidence: 99%
“…GSH offers protection against oxygen derived free radicals and cellular lethality following exposure to ionizing radiation [63]. Under normal conditions, the inherent defense system including glutathione and antioxidant enzymes protect against the oxidative damage [63,64]. A significant decline in GSH was noticed in irradiated control group as compared to normal.…”
Section: Discussionmentioning
confidence: 99%